1995
DOI: 10.1063/1.358870
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence and photoluminescence from chemical-vapor-deposited diamond

Abstract: Cathodoluminescence spectra from microwave-plasma-assisted chemical-vapor-deposited (CVD) diamond have been studied as a function of temperature at low electron energies. This investigation shows a pronounced difference between the luminescence spectra from CVD diamond films as grown and CVD diamond films annealed by rapid thermal processing at 1000 °C for one minute in an argon atmosphere. The relative intensities of the dominant features at 443 nm (2.8 eV) and 510 nm (2.4 eV) are very different for unanneale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…With the flood gun technique, it was most clearly shown that the "green" band was either dramatically reduced or completely eliminated. A similar decrease of this CL band was reported by Yang et al (1995). This resulted in a single dominant "blue" band in the spectra for all of the samples after processing.…”
Section: Box B: Cathodoluminescence Andx-ray Topography As Nondestrucsupporting
confidence: 85%
“…With the flood gun technique, it was most clearly shown that the "green" band was either dramatically reduced or completely eliminated. A similar decrease of this CL band was reported by Yang et al (1995). This resulted in a single dominant "blue" band in the spectra for all of the samples after processing.…”
Section: Box B: Cathodoluminescence Andx-ray Topography As Nondestrucsupporting
confidence: 85%
“…gap semiconductors is not uncommon as the near band-edge emission can be quenched by the defect energy states in the band gap. These emissions have been observed in the PL 8,14 and CL 9,15 analyses of CVD diamond films. The C K-edge XANES spectra recorded in total electron yield (TEY), X-ray fluorescence yield (FLY), and PLY (zero order) are displayed in Figure 2b.…”
mentioning
confidence: 68%
“…1,2 The photoluminescence (PL) excited by UV or visible light and cathodoluminescence (CL) excited by the electron beam from diamond thin films prepared by chemical vapor deposition (CVD) techniques have been widely studied. A sharp band at 1.68 eV [3][4][5] and several broad-band emissions at higher energies [6][7][8][9][10][11][12][13][14][15] from CVD diamond films have been reported. It is widely accepted that the sharp emission at 1.68 eV is related to defect centers involving silicon impurity in diamond.…”
mentioning
confidence: 99%
See 1 more Smart Citation